Toripalimab treatment of bladder-preserving therapy for locally advanced bladder cancer: a case report - Yang, Zhiyun; Liu, Yidao; Li, Ji; Wang, Xingsheng; Pan, Jun; Jiang, Jiafu; Zhang, Xingming (Frontiers in Oncology, 2025)
Neoadjuvant chemotherapy and radical cystectomy is the standard treatment for muscle invasive bladder cancer. For patients who are intolerant or unwilling to receive radical surgery and chemotherapy, the use of immune therapy combined with bladder preservation treatment has gradually become a viable treatment option. In this article, We aimed to present a case of cT2N0M0 Bladder cancer patient who was intolerant to chemotherapy and was treated with Toripalimab as a single-agent bladder preservation therapy for three cycles. After 15 months of treatment, a clinical complete response(cCR) was achieved, thus retaining the bladder. In this report, the safety profile of Toripalimab was favorable, with no severe or uncontrollable adverse events. The patient’s pathological IHC showed PD-L1 negative (TPS <1%, CPS <1%) and did not undergo mTURBT, which is a rare phenomenon. Our report suggests that Patients with PD-L1 negative but CD8+ T cell positive tumor infiltration can also benefit from PD-L1 inhibitor treatment and even achieve cCR to preserve the bladder.